Characterization of Plasmodium yoelii monoclonal antibodies directed against stage-specific sporozoite antigens. - Charoenvit, Y (1987)
A battery of monoclonal antibodies against Plasmodium yoelii sporozoites was produced. Five of these (NYS1 through NYS5) were selected for characterization. All five were positive in the indirect immunofluorescent antibody test with P. yoelii sporozoites; however, each showed a different immunofluorescence pattern. Although NYS1 (immunoglobulin G3 [IgG3]), NYS2 (IgG3), and NYS3 (IgM) were positive in the circumsporozoite precipitation test, only NYS1 and NYS2 were able to neutralize sporozoite infectivity in mice. NYS4 (IgM) and NYS5 (IgG1) were not positive in the precipitation test and did not protect mice from sporozoite infection. All except NYS4 were species as well as stage specific. NYS4 cross-reacted with sporozoites of P. berghei. Electrophoretic immunoblotting analysis showed that these monoclonal antibodies detected sporozoite antigens of various molecular weights. Inhibition enzyme-linked immunosorbent assays indicated that each recognized a different antigenic epitope. The differences in their immunochemical and biological reactivity make them useful for screening a variety of P. yoelii antigens in recombinant DNA libraries. These antigens will be used in an animal model system for vaccine development.